Betterment of ecological parameters of a diesel engine using Brown‘s gas - Rimkus, Alfredas; Pukalskas, Saugirdas; Matijošius, Jonas; Sokolovskij, Edgar (Journal of Environmental Engineering and Landscape Management, 2013)
Hydrogen could become an important element, allowing us to accumulate and transfer energy in a clean way. Hydrogen can be used in cars as a fuel additive which increases the combustion efficiency of the fuel-air mixture. A small amount of hydrogen gas could also be produced in a car by decomposing water by means of electrolysis, using for this purpose the energy produced by the car’s electric power generator. The hydrogen and oxygen (HHO) mixture obtained, which is also known as Brown’s gaseous mixture, is supplied to the engine’s intake manifold. Tests have been performed with 1.6 TD (SB) diesel engine. The automobile was tested on a chassis dynamometer running at a different speed. The engine was tested using fuel-air combustion mixture and fuel-air-HHO gas combustion mixture without additional adjustment of the fuel supply system. The test results have revealed that additional injection of HHO gas into combustion mixture resulted in up increase of fuel consumption, but the CO, the HC, the PM amount has decreased insignificantly. At few engine loads the amount of NOx decreased, however increasing the engine load resulted in a gradual increase. Having analysed test results we came to a conclusion that additional supply of HHO gas into combustion mixture resulted in improvement of the combustion quality of fuel-air mixture and ecological performance of the engine. This is especially relevant for the automobiles which are not equipped with a supplementary exhaust gas toxicity decreasing system. First published online: 11 Oct 2012